Pain and Narrative Shape: Beyond the Indocility of Trauma in Three Newfoundland Novels - María Jesús Hernáez Lerena (Atlantis, 2019)
This article looks at trauma beyond the fixation on the limits of narrative as expressed in the mainstream theory of trauma in the 1990s, in the work of Cathy Caruth, Shoshana Felman and Dori Laub, among others. Its purpose is to achieve an appreciation of narrative as a navigable textual itinerary whose very flows and discontinuities are energized by a reconciliation (or lack thereof) with life’s shocking and incomprehensible moments. I build upon Amir Khadem’s rejection of the polarity between narrative and the incurable psychic wound in order to provide textual analyses of a corpus of three contemporary novels set in the context of a historically traumatized regional identity, that of Newfoundland in Canada: The Town That Forgot How to Breathe (2003), by Kenneth J. Harvey, February (2009), by Lisa Moore, and Sweetland (2014), by Michael Crummey. A revision of the role of genres traditionally used to describe historical and personal crises will help us observe how their conventions function within a context of outrage at the global and regional mismanagement of natural resources.